Creating space for negotiating the nature and outcomes of collaborative research projects with Aboriginal communities - Lyons, Natasha (Études/Inuit/Studies, 2011)
This article investigates intellectual property and ethical issues involved in negotiating research processes and outcomes in collaborative projects with Aboriginal communities. A series of ideas are outlined to lay a foundation for thinking about ways to create a conceptual space for open and constructive discussions between research partners. Habermas’s notion of “communicative space” is applied to a partnership between southern-based anthropologists and members of the Inuvialuit community of the Canadian Western Arctic. This partnership is focused on documenting knowledge about a large and comprehensive collection of ancestral ethnographic objects housed at the Smithsonian Institution in Washington, D.C., and on disseminating this knowledge in meaningful ways to the Inuvialuit, anthropological, and museum communities. This article presents a suite of methods generated by the research group that lay some useful parameters for designing research and fostering trust and investment among partners. It also discusses the dynamics of community-based research practices and, specifically, methods for conceiving, constructing, and sustaining research projects.